Clinical features of influenza disease in admitted children during the first postpandemic season and risk factors for hospitalization: a multicentre Spanish experience. (10th January 2013) - Launes, C.; García‐García, J. J.; Martínez‐Planas, A.; Moraga, F.; Soldevila, N.; Astigarraga, I.; Arístegui, J.; Korta, J.; Quintana, J. M.; Torner, N.; Domínguez, A.; ,
Abstract: The main objectives of this study were to describe the characteristics of children with influenza infection during the postpandemic outbreak, and to compare sociodemographic and clinical data between patients who required hospitalization and those managed on an outpatient basis with a matched case–control study design. This is a multicentre paediatric study in Spain that included patients aged 6 month to 18 years in whom influenza infection was confirmed by real‐time reverse transcription–polymerase chain reaction between December 2010 and March 2011. Among the 143 admitted patients, the main reason for admission was respiratory failure (123/143). In 55 there was some previously known disease. The median age was lower in patients without comorbidity (1.8 years: interquartile range 1.0–3.0 versus 5.3 years: interquartile range 1.3–10.7); p <0.01). The lag time from onset of symptoms to starting antiviral treatment was correlated with the length of hospital stay (Rho Spearman = + 0.32; p 0.01). Twenty patients required admission to the paediatric intensive care units, all due to respiratory failure. Children with chest X‐ray opacities in more than one quadrant more frequently required admission to intensive care. Having a neurological disease conferred the highest risk of requiring hospitalization (OR 17.18) in a multivariate analysis. This study concludes that influenza in the paediatric population requiring hospitalization during the postpandemic season affected mainly children with neurological or pulmonary comorbidities and children of parents with a lower educational level. Most of the influenza infections caused respiratory symptoms, although neurological manifestations were also observed. Early initiation of oseltamivir was associated with a shorter length of hospital stay.